Hubungan Status Refraksi dengan Tekanan Intraokular Pada Pasien Glaukoma - Muhammad Wahyu Al-Fajri; Nur Khoma Fatmawati; Mona Zubaidah (ITKES Wiyata Husada Samarinda, 2022)
Refractive status is the ability of the eye to refract light on an objective or subjective refraction examination. Refractive status is divided into two category, emetropia and ametropia. Emetropia is normal refractive status and ametropia is refractive error include myopia, hypermteropia and astigmatism. Refractive error in Indonesia has become the most common disease in the eye. The factors that influence the changes in intraocular pressure (IOP) are refraction status, gender, diabetes mellitus (DM), hypertension and diurnal variation. Intraocular pressure is the main risk factor that causes glaucoma. Purpose of this study to investigate the correlation between refractive status and intraocular pressure in glaucoma patients at SMEC (Sabang Merauke Eye Center) Eye Clinic Samarinda. This research used analytical observational method with cross-sectional approach. 79 Samples were selected, consisting of 38 POAG patients, 18 PACG patients, and 23 NTG patients from the medical records at SMEC Samarinda. The data were gathered from the medical records using purposive sampling method. Glaucoma occurred mostly in female patients aged 40 years old and above. Astigmatism is the refractive status with the highest average of IOP observed in this research. The Chi-Square test showed that there was no correlation between refractive status and intraocular pressure, indicated by p-value of 0.374. There is no correlation between refractive status and intraocular pressure in glaucoma patients.